2020
DOI: 10.1101/2020.04.15.036285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome based Evolutionary study of SARS-CoV-2 towards the Prediction of Epitope Based Chimeric Vaccine

Abstract: SARS-CoV-2 is known to infect the neurological, respiratory, enteric, and hepatic systems of human and has already become an unprecedented threat to global healthcare system. COVID-19, the most serious public condition caused by SARS-CoV-2 leads the world to an uncertainty alongside thousands of regular death scenes. Unavailability of specific therapeutics or approved vaccine has made the recovery of COVI-19 more troublesome and challenging. The present in silico study aimed to predict a novel chimeric vaccine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…On this note, multi-epitope vaccine candidates have already been designed against several viruses, including MERS-CoV and SARS-CoV, and their efficacies have been further reported (Almofti et al, 2018;Ul Qamar et al, 2019;Yong et al, 2019). Two related studies have reported the in-silico design of epitope based chimeric vaccine candidates targeting E, M, S and N proteins of SARS-CoV-2, albeit not peer-reviewed (Yazdani et al, 2020;Akhand et al, 2020). Besides, Kibria, Ullah & Miah (2020) performed an immunoinformatic approach to design a 70 aa long multi-epitope vaccine focusing on the the virion outer surface proteins (E, M, and S) (Chan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On this note, multi-epitope vaccine candidates have already been designed against several viruses, including MERS-CoV and SARS-CoV, and their efficacies have been further reported (Almofti et al, 2018;Ul Qamar et al, 2019;Yong et al, 2019). Two related studies have reported the in-silico design of epitope based chimeric vaccine candidates targeting E, M, S and N proteins of SARS-CoV-2, albeit not peer-reviewed (Yazdani et al, 2020;Akhand et al, 2020). Besides, Kibria, Ullah & Miah (2020) performed an immunoinformatic approach to design a 70 aa long multi-epitope vaccine focusing on the the virion outer surface proteins (E, M, and S) (Chan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To determine epitope candidates in the design of the COVID-19 vaccine, researchers all over the world conducted a series of immunoinformatics analysis to predict B- and MHC class I/II T-cell epitopes from the Spike protein, M protein, E protein and N protein of the SARS-CoV-2 virus. We collected 24 published and pre-printed literature [ 14 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ] about the SARS-COV-2 epitopes from the outbreak of the epidemic to June 1, 2020 in total ( Supplementary Table 1 ). We discovered that the most frequently used B-cell linear epitope prediction methods were those provided on the Immune Epitope Database (IEDB) server including Bepipred [ 44 ], Kolaskar and Tongaonkar’s antigenic prediction [ 45 ], Emini’s surface accessibility prediction [ 46 ] ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Spike protein of SARS-COV-2 is regarded as the target due to its formation of characteristic crown of the virus and protruding from the viral envelope [ 15 ]. In order to determine the distribution of epitopes that may be used for vaccine construction, we integrated 24 published articles or preprints [ 14 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ] about epitope predictions from January 29, 2020 to June 1, 2020. Based on the results of these researches, we collected all the results about Spike protein for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed methods are provided in the online version of this paper and include the following: Baseline vaccine MHC I: (Srivastava et al, 2020) ( Srivastava et al, 2020) Figure 2 Baseline vaccine MHC I: (Herst et al, 2020) ( Herst et al, 2020) Data S1; Table 6 Baseline vaccine MHC I: (Herst et al, 2020)-top16 (Herst et al, 2020) Table 4 Baseline vaccine MHC I: (Baruah and Bose, 2020) ( Baruah and Bose, 2020) Table 1 Baseline vaccine MHC I: (Fast et al, 2020) ( Fast et al, 2020) Table 2 Baseline vaccine MHC I: (Poran et al, 2020) ( Poran et al, 2020) Table S5 Baseline vaccine MHC I: (Vashi et al, 2020) ( Vashi et al, 2020) Table 5 Baseline vaccine MHC I: (Abdelmageed et al, 2020) ( Abdelmageed et al, 2020) Table 2 Baseline vaccine MHC I: (Lee and Koohy, 2020) ( Lee and Koohy, 2020) Table 4 Baseline vaccine MHC I: (Akhand et al, 2020) ( Akhand et al, 2020) Table 2 Baseline vaccine MHC I: (Singh et al, 2020) ( Singh et al, 2020) Table 2 Baseline vaccine MHC I: (Bhattacharya et al, 2020) ( Bhattacharya et al, 2020) Table 2 Baseline vaccine MHC I: (Ahmed et al, 2020) Table 2 Baseline vaccine MHC I: (Saha and Prasad, 2020) ( Saha and Prasad, 2020) Table 1 Baseline vaccine MHC I: (Gupta et al, 2020) ( Gupta et al, 2020) 3 Baseline vaccine MHC II:…”
Section: Star+methodsmentioning
confidence: 99%
“…We used EvalVax to evaluate peptide vaccines and megapools proposed by other publications (Lee and Koohy, 2020;Fast et al, 2020;Poran et al, 2020;Bhattacharya et al, 2020;Baruah and Bose, 2020;Abdelmageed et al, 2020;Ahmed et al, 2020;Srivastava et al, 2020;Herst et al, 2020;Vashi et al, 2020;Akhand et al, 2020;Mitra et al, 2020;Khan et al, 2020;Banerjee et al, 2020;Ramaiah and Arumugaswami, 2020;Gupta et al, 2020;Saha and Prasad, 2020;Tahir ul Qamar et al, 2020;Singh et al, 2020;Yarmarkovich et al, 2020;Grifoni et al, 2020a;Nerli and Sgourakis, 2020;Yazdani et al, 2020;Ismail et al, 2020) on metrics including EvalVax-Unlinked and EvalVax-Robust population coverage at different per-individual number of peptide-HLA hits thresholds, expected per-individual number of peptide-HLA hits in White, Black, and Asian populations, percentage of peptides that are predicted to be glycosylated, peptides observed to mutate with a probability greater than 0.001, or peptides that sit on known cleavage sites. We define ''normalized coverage'' as the mean expected per-individual number of peptide-HLA hits for a vaccine divided by the number of peptides in the vaccine.…”
Section: Evalvax Evaluation Of Public Vaccine Designs For Sars-cov-2mentioning
confidence: 99%